Epidemiological aspects and control of the Cercospora leaf spot on cowpeas - Rios, Gerson Pereira; Zimmermann, Francisco José P. (Pesquisa Agropecuaria Brasileira, 2014)
The effects of some cultivation systems on Cercospora leaf spot development on cowpea and its control with benomyl were studied at the Centro Nacional de Pesquisa de Arroz e Feijão (CNPAF), Goiânia, GO. The cowpea treatments were 1) monocrop; 2) intercropped with corn; 3) intercropped with cassava, and 4) intercropped with sugarcane. The treatment with benomyl consisted of 0, 1, 2 and 3 sprayings. Incidence of Cercospora leaf spot was reduced when cowpeas were intercropped with corn as compared with monocrop or intercropped with cassava or sugarcane. One, two, and three benomyl sprayings reduced disease incidence by 20%, 30.9% and 40.6%, respectively, and resulted in grain yield increases of 14%, 24.2% and 35%. The form of disease progress curves was modified by benomyl spraying. The corresponding areas under the disease progress curves were not correlated with yield losses thowerer the number of lesions was negatively correlated with yield.